OS DESAFIOS DA IMPLANTAÇÃO DO ESOCIAL E SEUS REFLEXOS NAS ROTINAS DAS ORGANIZAÇÕES - VELLUCCI, ROSANA GRIBL (2017)
The advances in the area of Information and Communication Technology (ICT), especially with the emergence of the internet, provided changes in the relations between the Government and Society, giving origin to a new phase which has become known as Electronic Government or E-Gov. Taking advantage of this evolution and the experience of other countries, the Brazilian Federal Revenue Service (BFR) created the Public Digital Bookkeeping System (PDBS), of which eSocial is a component. In this context the present work has as objective verify if the changes coming from eSocial will demand the need of new routines in the area of personnel administration, through the verification of eSocial adaptability, the critical factors and the involvement of the Direction with the implementation of this project by the organizations. In order to achieve this objective, an exploratory, descriptive and transversal research with a quantitative approach was carried out involving 61 companies. A descriptive analysis of the data was performed, revealing that the majority of the respondents are between 40% and 60% adapted to eSocial, , Regarding the involvement of management with eSocial, the average result of 3,10, revealed medium involvement and as for the critical factors, it was possible to identify that there are customary practices, ranging from sometimes until always, on the part of these companies, in disagreement with labor and social security legislation. Through the application of an exploratory factorial analysis (EFA), it was possible to verify that eSocial adaptability is formed by three dimensions that are represented by 11 variables and that the involvement of the management is one-dimensional and composed of five variables. Through Spearman's correlation test, it was possible to identify that there is a moderate, significant and positive association between the involvement of the management and the adaptability to the eSocial, being possible to prove the hypothesis one (H1+) of this research "the greater the involvement of management with the implementation of eSocial, the higher will be the level of adaptability of the company in the implementation of eSocial." Finally, considering the viability of labor and social security rights guarantee that is one of the principles that guides the eSocial, as well as any increase in the inspection and cross-checking of information capacity that eSocial will bring to the inspection process, it’s evident the need for changes in personnel management practices of organizations, in order to avoid the discomfort of being negatively impacted, with the application of administrative fines and other penalties for non-compliance with legal requirements.